2012
DOI: 10.1590/s1806-83242012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of artificial saliva in biofilm formation of Candida albicans in vitro

Abstract: Due to the increase in life expectancy, new treatments have emerged which, although palliative, provide individuals with a better quality of life. Artificial saliva is a solution that contains substances that moisten a dry mouth, thus mimicking the role of saliva in lubricating the oral cavity and controlling the existing normal oral microbiota. This study aimed to assess the influence of commercially available artificial saliva on biofilm formation by Candida albicans. Artificial saliva I consists of carboxym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 26 publications
1
21
0
3
Order By: Relevance
“…However, a previous study has demonstrated that a similar concentration range of lysozyme (6–100 µg/ml) significantly inhibited C. albicans biofilm formation on an acrylic resin surface (33). In contrast, a separate study demonstrated no significant reduction in C. albicans attachment on acrylic resin disks immersed in a solution containing lysozyme, lactoferrin and glucose oxidase complex/lactoperoxidase (35). These conflicting observations are consistent with the present study, where the susceptibility of C. albicans wild strains to lysozyme differed from one another.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, a previous study has demonstrated that a similar concentration range of lysozyme (6–100 µg/ml) significantly inhibited C. albicans biofilm formation on an acrylic resin surface (33). In contrast, a separate study demonstrated no significant reduction in C. albicans attachment on acrylic resin disks immersed in a solution containing lysozyme, lactoferrin and glucose oxidase complex/lactoperoxidase (35). These conflicting observations are consistent with the present study, where the susceptibility of C. albicans wild strains to lysozyme differed from one another.…”
Section: Discussionmentioning
confidence: 94%
“…The in vitro effect of lysozyme on C. albicans biofilms remains controversial: certain studies demonstrated no beneficial effect of artificial saliva-containing lysozyme and other salivary proteins on yeast adhesion to acrylic resin (35), while others demonstrated a preventive role for lysozyme with respect to C. albicans biofilm formation on dentures (33). To the best of our knowledge, no studies have explored the link between C. albicans biofilm formation and lysozyme agglutination properties, previously described at 1 mg/ml concentration (22).…”
Section: Introductionmentioning
confidence: 99%
“…In the production of herbal medicines, the extraction process and choice of an appropriate solvent are important [22]. In the present study, the maceration method was chosen due to several advantages including a minimal amount of organic solvent and the ability to maintain the extraction temperature below the solvent boiling point to avoid degradation of the oil component by heating [23].…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al 28 Nesse estudo in vitro foi utilizada uma coloração diferencial e microscopia eletrônica de varredura (SEM) para avaliar o efeito do hipoclorito de sódio e do gluconato de clorhexidina na viabilidade, remoção e morfologia do biofilme de C. albicans em prótese acrílica.…”
Section: Metodologia Aplicada Resultados Referênciaunclassified
“…Esse microrganismo leveduriforme não é prejudicial em seres humanos saudáveis, mas pode ocasionar infecções oportunistas em pacientes imunocomprometidos, resultando em candidíase 25 principalmente na idade senil, quando se faz necessário o uso de próteses artificiais que causam mudanças no ambiente e na flora oral 26 . A patogenicidade da Candida foi associada a diversos fatores de virulência, englobando adesão a células hospedeiras ou dispositivos médicos e secreção de enzimas hidrolíticas, como proteases, fosfolipases e hemolisinas 27,28 . Além disso, os principais fatores determinantes do curso infeccioso são saliva, formação de biofilmes e natureza do substrato, que pode variar individualmente e em relação ao tipo de microrganismo 2 .…”
Section: Espécies De Candida Formadoras De Biofilme Em Resinas Acrílicasunclassified